Markers of the Validity of Reported Energy Intake - Livingstone, M. Barbara E.; Black, Alison E. (The Journal of nutrition, 2003)
Energy intake (EI) is the foundation of the diet, because all other nutrients must be provided within the quantity of food needed to fulfill the energy requirement. Thus if total EI is underestimated, it is probable that the intakes of other nutrients are also underestimated. Under conditions of weight stability, EI equals energy expenditure (EE). Because at the group level weight may be regarded as stable in the timescale of a dietary assessment, the validity of reported EI can be evaluated by comparing it with either measured EE or an estimate of the energy requirement of the population. This paper provides the first comprehensive review of studies in which EI was reported and EE was measured using the doubly labeled water technique. These conclusively demonstrate widespread bias to the underestimation of EI. Because energy requirements of populations or individuals can be conveniently expressed as multiples of the basal metabolic rate (BMR), EE:BMR, reported EI may also be expressed as EI:BMR for comparison. Values of EI:BMR falling below the 95% confidence limit of agreement between these two measures signify the presence of underreporting. A formula for calculating the lower 95% confidence limit was proposed by Goldberg et al. (the Goldberg cutoff). It has been used by numerous authors to identify individual underreporters in different dietary databases to explore the variables associated with underreporting. These studies are also comprehensively reviewed. They explore the characteristics of underreporters and the biases in estimating nutrient intake and in describing meal patterns associated with underreporting. This review also examines some of the problems for the interpretation of data introduced by underreporting and particularly by variable underreporting across subjects. Future directions for research are identified.